Layanan Bimbingan Klasikal Menggunakan Teknik Brainstorming Untuk Meningkatkan Keaktifan Berkomunikasi Siswa - Mainilawati; M.Ferdiansyah; Kurnia Sari (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2020)
Communication is an important student competency in 4.0 learning process, especially for students of SMA Patra Mandiri 1 Palembang. Students X MIPA 1 especially, need to be stimulated to be active in communicating in the classroom. This research aims to test the development of students' active communication through brainstorming in classical guidance activities. Research use a quasi experimentation method with one group time-series design. The research design uses one group of experiments without any control group comparison centered on only one group, over time. Sampling technique using census sample, and obtained a sample of 21 students X MIPA1 SMA Patra Mandiri 1 Palembang. The research data was obtained using a questionnaire of student communication that was shared through the google form. Analyze data using the Wilcoxon sign rank test. The results showed brainstorming techniques were effective in improving students' active communication, as evidenced by Zstat=253 < Zcrit=389. The recommendations of this study are 1) the use of time needs to be optimized, so that there are not many pauses that cause students to become passive, 2) brainstorming techniques can be combined with brainwriting so that all students have the opportunity to express an opinion